When a buyback isn’t a buyback: open market repurchases and employee options - Kahle, Kathleen M (Journal of Financial Economics, 2002)
This paper examines how stock options affect the decision to repurchase shares. Firms announce repurchases when executives have large numbers of options outstanding and when employees have large numbers of options currently exercisable. Once the decision to repurchase is made, the amount repurchased is positively related to total options exercisable by all employees but independent of managerial options. These results are consistent with managers repurchasing both to maximize their own wealth and to fund employee stock option exercises. The market appears to recognize this motive, however, and reacts less positively to repurchases announced by firms with high levels of nonmanagerial options.